Megalotremis oleosa (Lichenized Ascomycota: Monoblastiaceae), a new lichen species with inspersed hamathecium from the dwarf forest of the southern Philippines - Taer, Ermalene C.; Aptroot, André; Amoroso, Victor B.; Forno, Manuela Dal (Phytotaxa, 2026)
N/A